Farmers’ Awareness is a Key Factor for Profitable Crop Production - Iqbal, Muhammad Naeem; Ashraf, Asfa (PSM Biological Research, 2022)
Farmers play a central role in ensuring a sustainable agricultural system, which results from farmers’ knowledge and expectations. Even though farmers received agricultural information, they could not apply the information to crop production. There are several practical areas of concern regarding water resources, basic machinery, and the lack of formal extension provision in the area. In this issue, Haider et al. (2022) report that almost all the farmers were not aware of the best practices of rice cultivation in areas with fewer water supplies. No information was provided to the farmers by the extension field staff as there were no field assistants in the research area. Farmers’ awareness of cultivation can be increased through developing extension services programs to distribute useful information on crop production effectively. Farmers’ awareness, farmer skills, and management to operate along with the adoption of technologies that have the potential to contribute to sustainable farming systems will help to meet growing demands for food, to be internationally competitive, and to produce agricultural products of high quality.